Empire of the Sun : a novel - Ballard, J. G., 1930- (New York : Simon and Schuster, 1984)
Jim, an eleven-year-old British schoolboy, lives in Shanghai in 1941. He relates his experiences which include three years spent in Lunghus, a Japanese prison camp, before being reunited with his parents and returning to England.
Sequel: The kindness of women.
Young Adult.
Keywords: Boys -- China -- Shanghai -- Fiction; World War, 1939-1945 -- China -- Shanghai -- Fiction; Shanghai (China) -- History -- Fiction; World War, 1939-1945 -- Fiction